Angio-osteogenic capacity of octacalcium phosphate co-precipitated with copper gluconate in rat calvaria critical-sized defect. Issue 1 (31st December 2022) - Koyama, Shinki; Hamai, Ryo; Shiwaku, Yukari; Kurobane, Tsuyoshi; Tsuchiya, Kaori; Takahashi, Tetsu; Suzuki, Osamu
ABSTRACT: The objective of this study is to investigate the effects of octacalcium phosphate (OCP)-induced bone regeneration on angiogenesis regulated by the inclusion of copper ions in OCP in vitro and in vivo. Calcium (Ca)-deficient Cu-OCPs, containing 0.01 wt% Cu (low-Cu-OCP) and 0.12 wt% Cu (high-Cu-OCP), were synthesized with co7pper gluconate salt. The lattice parameters of Cu-OCPs tended to decrease slightly with Cu inclusion, as estimated by Rietveld analysis. Cu ions were released in OCP when the materials were incubated in the medium for human umbilical vein endothelial cells (HUVECs). The solubility of Cu-OCPs, estimated by the degree of supersaturation, was slightly higher than that of the original OCP. Cu-OCP tended to hydrolyze to an apatite structure while maintaining the crystal plate-like morphology when incubated with mesenchymal stem D1 cells in osteogenic media for 14 days. The specimens were characterized by selected area electron diffraction, transmission electron microscopy, and Fourier transform infrared spectroscopy. Low-Cu-OCP significantly enhanced the HUVEC capillary cross-linking density. D1 cell differentiation was inhibited with the inclusion of Cu, even at low concentrations. The composite of low-Cu-OCP with a gelatin sponge (low-Cu-OCP/Gel) significantly enhanced angiogenesis coupled with bone regeneration when implanted in a rat calvarial critical-sized defect for 4 weeks, compared with the corresponding amount of Cu-containing Gel (Cu/Gel) or OCP/Gel materials through angiography and tissue histomorphometry. These results support the proposition that angiogenesis stimulated by low-Cu-OCP is closely related with enhanced bone regeneration. Graphical abstract: uf0001